2017
DOI: 10.1021/acs.bioconjchem.7b00566
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Centyrin-Based Near-Infrared Probe for Fluorescence-Guided Surgery of Epidermal Growth Factor Receptor Positive Tumors

Abstract: Tumor-targeted near-infrared fluorescent dyes have the potential to improve cancer surgery by enabling surgeons to locate and resect more malignant lesions where good visualization tools are required to ensure complete removal of malignant tissue. Although the tumor-targeted fluorescent dyes used in humans to date have been either small organic molecules or high molecular weight antibodies, low molecular weight protein scaffolds have attracted significant attention because they penetrate solid tumors almost as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 60 publications
0
23
0
Order By: Relevance
“…This has indeed been shown in a dose-escalation study in patients with IR800conjugated cetuximab where higher TBRs were obtained with the highest injection dose (30), as well as with a fluorescent diabody targeting an antiprostate stem cell antigen (31). However, numerous studies have reported better TBRs with lower doses because increasing the injection amount also leads to more nontarget uptake that reduces contrast, increases the number of falsepositives, and negatively affects specificity (32)(33)(34)(35). In order to examine this effect with Ga-MMC(IR800)-TOC, xenografts were injected with 0.5 or 2 nmol and showed a direct correlation between injected dose and absolute fluorescence in tumor and normal tissues.…”
Section: Discussionmentioning
confidence: 73%
“…This has indeed been shown in a dose-escalation study in patients with IR800conjugated cetuximab where higher TBRs were obtained with the highest injection dose (30), as well as with a fluorescent diabody targeting an antiprostate stem cell antigen (31). However, numerous studies have reported better TBRs with lower doses because increasing the injection amount also leads to more nontarget uptake that reduces contrast, increases the number of falsepositives, and negatively affects specificity (32)(33)(34)(35). In order to examine this effect with Ga-MMC(IR800)-TOC, xenografts were injected with 0.5 or 2 nmol and showed a direct correlation between injected dose and absolute fluorescence in tumor and normal tissues.…”
Section: Discussionmentioning
confidence: 73%
“…This was further confirmed after loading the Adnectin with 64 Cu where the monobody was able to provide same-day PET visualisation of tumour cells, resulting in an increase in the monobody uptake in tumours over 24 h post-injection [62,69]. This concept has been taken even further with a Centyrin domain evolved to bind EGFR and conjugated with a fluorescent dye, which was then applied to guide surgical removal of tumour cells [70].…”
Section: Biosensorsmentioning
confidence: 78%
“…This was further confirmed after loading the Adnectin with 64 Cu where the monobody was able to provide same-day PET visualisation of tumour cells, resulting in an increase in the monobody uptake in tumours over 24 hours postinjection [61,68]. This concept has been taken even further with a Centyrin domain evolved to bind EGFR and conjugated with a fluorescent dye, which was then applied to guide surgical removal of tumour cells [69].…”
Section: Biosensorsmentioning
confidence: 78%